2014
DOI: 10.1002/pssa.201431145
|View full text |Cite
|
Sign up to set email alerts
|

Doping strategies for highly conductive Al-doped ZnO films grown from aqueous solution

Abstract: Aluminum‐doped zinc oxide (AZO) thin films are prepared by a low temperature (100 °C) aqueous solution deposition method with a subsequent UV post‐deposition treatment at 140 °C. Film growth is governed by the retrograde solubility of zinc–ammine complexes at basic conditions (pH 11.4). Aluminum was introduced into the film as a dopant by co‐precipitation, either using an aluminum metal foil or aluminum nitrate as a precursor. As the presence of Al ions in the solution influences the film morphology as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…The most prominent absorption peak is located at 1117 cm -1 and corresponds to the Si-O stretching vibration of the substrate (m SiO ) [27]. Further peak assignment was conducted according to the literature [28]. A broad minimum located around 3600 cm -1 is observed, which can be attributed to O-H stretching vibrations (m OH ).…”
Section: Stability Under Uv Irradiation and Increased Temperaturementioning
confidence: 99%
“…The most prominent absorption peak is located at 1117 cm -1 and corresponds to the Si-O stretching vibration of the substrate (m SiO ) [27]. Further peak assignment was conducted according to the literature [28]. A broad minimum located around 3600 cm -1 is observed, which can be attributed to O-H stretching vibrations (m OH ).…”
Section: Stability Under Uv Irradiation and Increased Temperaturementioning
confidence: 99%
“…Since the price for the most commonly used TCO Indium Tin Oxide (ITO) rises enormously due to a rapidly growing demand and rare earth abundance of Indium, a cost effective alternative with comparable quality is needed. Aluminum Zinc Oxide (AZO) as alternative TCO reaches the most interest, because the precursors are nontoxic, cheap and earth-abundant [1,2,3]. There are diverse established physical and chemical techniques as sputtering, evaporation, pulsed laser deposition, chemical vapour deposition or sol-gel technique to deposit thin TCO films directly on substrate [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This concept was used by several groups to deposit intrinsic [9] and doped ZnO thin films [10][11][12][13][14]. The key to obtain dense materials rather than nanorods was in all approaches the use of citrate as structuredirecting agent, which selectively decelerates crystal growth along the ZnO c-axis [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Hagendorfer et al reported Al-doped ZnO layers with resistivity values in the range of 10 -3 X cm, using the aforementioned CBD chemistry. To achieve low resistivity values, ultraviolet (UV)-light annealing instead of thermal annealing was used, permitting to maintain the temperature below 85°C during the whole production process [10,11].…”
Section: Introductionmentioning
confidence: 99%